THE EFFECT OF COMMUNITY PHARMACIST’S COUNSELING ON HYPERTENSIVE PATIENTS - Muvita Rina Wati; Mustofa Mustofa; Ika Puspita Sari (Faculty of Pharmacy, Universitas Gadjah Mada)
The role of pharmacists in health care has shifted not only providing medicine but also adjust the individual needs of patient,including counseling. This study aimed to determine the relationship between pharmacist counseling on the patients knowledgeabout hypertension and its treatment, patients adherence in taking antihypertensive medication, and the relationship between patientcompliance in the therapeutic target hypertensive patients.The study was conducted in UGM Pharmacy with two groups design, intervention and control, and pretest-posttest design using consecutive sampling method from hypertensive patient between July to December 2014. The data included bloodpressure, gender, age, education level, body mass index, the duration of patients suffered hypertension, other symptoms, presence ofcomorbidities, smoking status and alcohol consumtion, daily exercise, insomnia, stress, adherence measured using Morisky MedicationAdherence Scale (MMAS), and knowledge level about hypertension and its treatment.The study were followed by 76 people, consisted of 38 people in the intervention group and 38 in the control group. Characteristicsof the subjects were normally distributed between the two groups except the sex (p = 0,027) and stress levels (p=0,016). The counselingby a pharmacist in the intervention group significantly improved patient compliance (p=0,000) and increased patient knowledge(p=0,003) in the intervention group. Medication adherence in hypertensive patients showed that the achievement of targeted therapiesof systolic blood pressure (p=0,001) and diastolic (p=0,001) increased significantly.Keywords: hypertension, pharmacist, counselung, compliance.Keywords: hypertension, pharmacist, counseling, compliance